ECONOMIC FREEDOM AND ECONOMIC DEVELOPMENT: THEORETICAL-EMPIRICAL RESEARCH OF CONNECTION - Markovych, Iryna (Journal of European Economy, 2017)
The article analyzes the existing theoretical and empirical approaches to the concept of economic freedom and its importance in the evolution of the country. The results of the identification of dependencies between indicators of economic freedom of the countries and individual indicators of their economic development were discovered. It was found the typical direct links between the expansion of economic freedom and the welfare of the population for the majority of the countries.